To survive in the COVID-19 pandemic: The financial aspects of NGOs - Halina Waniak-Michalak; Sviesa Leitoniene; Ivana Perica (Contemporary Economics, 2024)
On the one hand, during the COVID-19 pandemic, NGOs are under pressure to provide more support. On the other hand, these organisations are facing new challenges that limit their activities, for example, a lack of volunteers and the inability to continue programs, raise funds, and serve beneficiaries. Despite these challenges, some NGOs have been forced to close down, while others have successfully collected funds and developed their activity. Therefore, this article aims to research how NGOs changed their funding models to overcome fundraising problems during the COVID-19 pandemic . The study investigated the impact of the COVID-19 pandemic on various non-profits in Poland, Lithuania, Croatia, and the United Kingdom. The results of the content analysis showed that critical success factors were: additional projects, public funds, collaboration with the government, the use of grants, additional funding from the funder, virtual fundraising and campaigning, collaboration with other NGOs, combined resources, implementation of joint projects, and the cooperation with the funders. The logistic regression analysis results supported the hypothesis that the financial success of NGOs during the COVID-19 pandemic depended on a change in the funding model and on a shift in financing from the corporate founder. However, despite the better financial results of NGOs, non-financial results were worse in times of crisis.
Keywords: L31; L38; L39; 330; nongovernmental organisations; NGOs; COVID-19 pandemic; mission models; fundraising